Impact of COVID-19 in paediatric early-phase cancer clinical trials in Europe: A report from the Innovative Therapies for Children with Cancer (ITCC) consortium. (December 2020) - Rubio-San-Simón, Alba; André, Nicolas; Cefalo, Maria Giuseppina; Aerts, Isabelle; Castañeda, Alicia; Benezech, Sarah; Makin, Guy; van Eijkelenburg, Natasha; Nysom, Karsten; Marshall, Lynley; Gambart, Marion; Hladun, Raquel; et al.
Abstract: Introduction: Data regarding real-world impact on cancer clinical research during COVID-19 are scarce. We analysed the impact of the COVID-19 pandemic on the conduct of paediatric cancer phase I–II trials in Europe through the experience of the Innovative Therapies for Children with Cancer (ITCC). Methods: A survey was sent to all ITCC-accredited early-phase clinical trial hospitals including questions about impact on staff activities, recruitment, patient care, supply of investigational products and legal aspects, between 1st March and 30th April 2020. Results: Thirty-one of 53 hospitals from 12 countries participated. Challenges reported included staff constraints (30% drop), reduction in planned monitoring activity (67% drop of site initiation visits and 64% of monitoring visits) and patient recruitment (61% drop compared with that in 2019). The percentage of phase I, phase II trials and molecular platforms closing to recruitment in at least one site was 48.5%, 61.3% and 64.3%, respectively. In addition, 26% of sites had restrictions on performing trial assessments because of local contingency plans. Almost half of the units suffered impact upon pending contracts. Most hospitals (65%) are planning on improving organisational and structural changes. Conclusion: The study reveals a profound disruption of paediatric cancer early-phase clinical research due to the COVID-19 pandemic across Europe. Reported difficulties affected both patient care and monitoring activity. Efforts should be made to reallocate resources to avoid lost opportunities for patients and to allow the continued advancement of oncology research. Identified adaptations to clinical trial procedures may be integrated to increase preparedness of clinical research to futures crises. Highlights: The COVID-19 pandemic has profoundly disrupted paediatric cancer clinical research. A drastic drop in recruitment in phase I/II trials compared with that in 2019 was observed. Current research needs reorganisation to avoid loss of opportunities for children.